Determination of Salmonella enterica Leaf Internalization Varies Substantially According to the Method and Conditions Used to Assess Bacterial Localization - Chahar, Madhvi; Kroupitski, Yulia; Gollop, Rachel; Belausov, Eduard; Melotto, Maeli; Sela-Saldinger, Shlomo (Frontiers in Microbiology, 2021)
Leaf internalization is an important trait of both plant- and human-pathogens that colonize plants. Salmonella enterica was reported to efficiently internalize the leaves of multiple plants, including tomato. In a previous study, comparing the internalization of S. enterica serovar Typhimurium in various leaves by confocal microscopy, we have demonstrated that the pathogen failed to internalize tomato leaves. Numerous reasons may account for these findings, yet one such factor might be the methodology employed to quantify leaf internalization. To this end, we have systematically studied leaf localization of a GFP-labelled Salmonella strain in tomato, lettuce, and Arabidopsis leaves, previously shown to support different levels of Salmonella internalization. Three protocols were employed for surface sterilization and enumeration of the surviving bacteria, side by side, with confocal microscopy observations. Leaf sterilization was performed using either sodium hypochlorite, silver nitrate, or ethanol, for 1 to 7 min. The same surface sterilization protocols resulted in different inactivation levels of Salmonella thus affecting the quantification of apparent internalization in the three tested leaves. The level of internalization varied according to the type of disinfectant and the treatment time. Treatment of tomato leaves with 70% ethanol for up to 7 min suggested possible internalization of Salmonella, while confocal microscopy showed no internalization. The lack of Salmonella internalization in tomato leaves seemed to corroborated our previous finding using a different tomato cultivar. Finally, both the plate count technique and confocal microscopy demonstrated considerable Salmonella internalization in lettuce and Arabidopsis leaves thought different sterilization conditions resulted in variations in the internalization levels. Our findings highlighted the dependency of the internalization results on the specific disinfection protocol used to determine bacterial localization. Altogether, this is the first systematic study comparing the effect of the same leaf sterilization protocols on the internalization level of Salmonella in leaves of different plants, side by side with confocal microscopy analysis. The results underscore the importance of confocal microscopy in validating a particular surface sterilization protocol whenever a new pair of bacterial strain and plant cultivar is studied.